From natural history to science: display and the transformation of American museums of science and nature - Karen A. Rader; Victoria E. M. Cain (Museum & Society, 2008)
This paper explains how and why many American museums of science and nature moved away from the traditional content and methods of natural history in the period from 1930 to 1980. It explores diverse motivations for the shift from dead, stuffed displays to live, interactive exhibits, and the consequences of that shift for museums as both educational institutions and as institutions of research. Ultimately, it argues that debates over museums’ content and display strategies drew strength from and reinforced a profound transformation in the institutional history of twentieth-century American science and technology: namely, the separation of research and public education. By the late 1960s, the American museum landscape had been transformed by this development. Older natural history museums competed for visitors and resources with ‘new’ style science museums, and although both remained popular cultural institutions, neither had achieved a coherent new institutional identity because debates about the role of the museum in science continued. Thus, we suggest, in the mid-twentieth century natural history and science museums were more important in both the history of biology and the history of science’s public culture than has previously been acknowledged.